Regional economic integration in Asia: The track record and prospects - Razeen Sally (European Centre for International Political Economy (ECIPE), 2010)
This is the season for regional-integration initiatives in Asia. There is talk of region-wide FTAs, and there are east-Asian initiatives on financial and monetary cooperation. But grand visions for Asian regional blocs are not achievable. Regional economic integration is most developed in east Asia, but only because of manufacturing supply chains linked to global markets. South Asia is the most malintegrated region in the world. And east and south Asia are much less integrated in finance than they are in trade and FDI - due to highly restrictive national policies governing financial markets. Asia's existing FTAs are "trade light". They are largely limited to tariff cuts, but have barely tackled non-tariff regulatory barriers in goods, services and investment, and are bedevilled by complex rules of origin requirements. An APEC FTA initiative has gone nowhere - entirely predictable given such a large, heterogeneous grouping. An east-Asian or a pan-Asian FTA, by discriminating against third countries, would compromise regional production networks linked to global supply chains. Moreover, huge economic gaps and enduring political differences will stymie Asian regional integration for some time to come. As for regional monetary and financial cooperation, it is embryonic, very soft and confined to east Asia. Asian regional integration is not likely to come about through top-down regional policy initiatives. The key to future regional and global integration is renewed unilateral, non-discriminatory liberalisation, this time going beyond border barriers to tackle behind-the-border regulatory barriers. That, more than anything else, would extend multinationals' supply chains in the region, and open up regional markets for domestic producers and consumers. Asian regional institutions can be useful at the margin. They can be "chat forums" for policy dialogue and exchange of information, gradually improve mutual surveillance and transparency, promote trade facilitation and "best-practice" measures, and (at best) cement unilateral liberalisation and help to prevent its reversal in difficult times. But more ambitious regional initiatives are inadvisable, indeed unachievable. Better, therefore, to be pragmatic and realistic - and stick to terra firma.
Keywords: 330; Globalisierung; Internationale Wirtschaftsbeziehungen; Internationale Unternehmenskooperation; Wirtschaftsintegration; Asiatisch-pazifischer Raum